ANALYSIS OF TENDENCIES AND TRENDS IS IN DESIGN OF INTERFACES OF MODERN MOBILE ADDITIONS - Пустюльга , С. І.; Самчук, В. П.; Шаповалова, А. А.; Клак, Ю. В. (Art and Design, 2024)
The purpose of the study is to critically review current trends in the design of mobile application interfaces and to identify the main trends in the design of applications for users of different age categories. Methodology. The research is based on a comprehensive analysis of information sources in the field of interface design, using the method of comparing the main trends in the design of modern mobile applications and the method of synthesis in developing recommendations for improving the application interface for different categories of users. Results. To achieve this goal, we analyzed and compared more than 50 mobile applications of different categories and identified their common features, as well as popular interface design techniques. The experience and recommendations of leading designers and experts in the field of mobile design were studied and analyzed. The article explores the main trends in mobile application design, in particular: the use of simple and clean interfaces; the use of minimalist design; the use of neutral colors and simple design elements; the introduction of material design ideas that use visual effects to give the illusion of a realistic surface and depth. The effectiveness of using gradients and various color transitions, which allow creating more complex and dynamic interfaces, is analyzed. The use of animations, which add liveliness and dynamism to applications and greatly facilitate the user's understanding of the processes in the application, is investigated. It has been determined that to improve the user experience of mobile applications, it is necessary to adhere to the principles of convenience and accessibility, to take into account the needs and expectations of users of different age categories, and to actively use the latest technologies. Scientific novelty. A critical analysis of current trends in the design of mobile application interfaces is carried out. The main most popular design trends for users of different age categories are highlighted. New possibilities for introducing the functionality of design systems, i.e. a set of rules, components, and other resources used to create application design, into the design of mobile applications are considered. Practical significance. The results of the study can be useful for mobile application developers who want to improve the user experience and increase the number of users. Practical recommendations allow for more efficient creation of mobile applications that will meet the needs of users of different age groups and meet modern trends in interface design.